2018
DOI: 10.4314/sajas.v48i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of <i>Lablab purpureus</i> and Vigna unguiculata and their subsequent effects on methane production in Xhosa lop-eared goats

Abstract: The objective of this study was to evaluate the nutritive value and anti-nutrient contents of Lablab purpureus (Lablab) and Vigna unguiculata (cowpea) and their effects on methane production in goats. Legume forages were grown and harvested at three stages of growth of pre-anthesis, anthesis, and post anthesis. Samples were collected at each stage and examined for proximate composition, total phenolics, condensed tannins, and saponins using standard methods. Hay was harvested at the anthesis stage and used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
4
12
2
1
Order By: Relevance
“…The results in the current study could be ascribed to the fact that, female goats generally consumed more feed than male goats; hence DMI was higher in females than in males, as a result of that, male goats emitted less methane gas than female gas. Findings in the current study contradict that of [37], who reported that male goats produced more methane gas than female goats. This could be possible due to the fact that males animals normally, are the ones that usually consume more feed (higher DMI) than female animals, thus that was the case with [37].…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 99%
See 3 more Smart Citations
“…The results in the current study could be ascribed to the fact that, female goats generally consumed more feed than male goats; hence DMI was higher in females than in males, as a result of that, male goats emitted less methane gas than female gas. Findings in the current study contradict that of [37], who reported that male goats produced more methane gas than female goats. This could be possible due to the fact that males animals normally, are the ones that usually consume more feed (higher DMI) than female animals, thus that was the case with [37].…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 99%
“…Findings in the current study contradict that of [37], who reported that male goats produced more methane gas than female goats. This could be possible due to the fact that males animals normally, are the ones that usually consume more feed (higher DMI) than female animals, thus that was the case with [37]. The result in gure 1, 2, 3 and 4 show that methane production was not consistent with time.…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 99%
See 2 more Smart Citations
“…CP) 0,049 b 0,024 a 0,036 ab 0,044 b 0,033 ab 0,004 Keterangan: 1) WFS 0 = Wafer ransum limbah inkonvensional tanpa biofermentasi dan suplementasi, WF 1 S 11 = WFS 0 terfermentasi 1,5% cairan rumen dan disuplementasi 0,15% multivitamin-mineral dan 5 % lemak hewan, WF 2 S 12 = WSF 0 terfermentasi 3,0% cairan rumen dan disuplementasi 0,15% multivitamin-mineral dan 10 % lemak hewan, WF 1 S 21 = WFS 0 terfermentasi 1,5% cairan rumen dan disuplementasi 0,30% multivitamin-mineral dan 5 % lemak hewan, dan WF 2 S 22 = WFS 0 terfermentasi 3,0% cairan rumen dan disuplementasi 0,30% multivitamin-mineral dan 10 % lemak hewan, 2) Hurup yang sama pada baris sama, berbeda tidak nyata (P>0.05), 3) SEM = Standard Error of The Treatment Means peningkatan kecernaan nutrien ransum (Tabel 5) sehingga nutrien yang tersedia dapat dimanfaatkan dengan baik untuk produktivitas ternak, serta nutrien terbuang yang terbuang dalam wujud emisi polutan melalui feses maupun gas hasil metabolisme rumen berkurang. Hal ini sejalan dengan laporan Washaya et al (2018) yang menunjukkan pemberian ransum yang mempunyai kecernaan lebih tinggi dapat menurunkan emisi metana (% digestibel energi) dari 12,0% menjadi 10,3% sampai 8,0%. Hal ini disebabkan karena hijauan legum dapat mengurangi produksi metana enterik secara signifikan pada kambing.…”
Section: Pendahuluanunclassified